Increasing the effectiveness of the capacity usage at rolling stock service locations. (March 2022) - van Hövell, Madeleine E.M.A.; Goverde, Rob M.P.; Bešinović, Nikola; de Weerdt, Mathijs M.
Abstract: Trains consist of one or more railway vehicles called rolling stock, which need interior and exterior cleaning and small technical checks on a daily basis. These services are executed at service locations (SLs). Scheduling rolling stock servicing tasks during an operational day is important to guarantee the fulfilment of servicing deadlines. Public transport companies face large scheduling problems, especially those with 24-hour-a-day operation. The expected increase in transport frequencies enhances the need for improving scheduling servicing tasks during an operational day. Therefore, the Rolling Stock Servicing Scheduling Problem (RS-SSP) is modelled comprising a MILP model. Complying with the planned timetable, the RS-SSP maximises the RS units being serviced during daytime. The RS-SSP allows RS exchanges between RS units having completed servicing and operating RS units requiring servicing. Due to this RS Exchange Concept, the number of RS units visiting the SL during daytime can be increased. The proposed RS-SSP model has been tested on a real-life case from the Dutch railways. For multiple scenarios, the model was able to exchange all running RS. Consequently, the capacity usage at SLs can be increased by the RS-SSP by shifting some of the excessive workload to daytime, and thus solving the capacity shortages. Highlights: A new Rolling Stock (RS) exchange concept, providing possibilities of exchanging rolling stock during daytime. A new mathematical model Rolling Stock Servicing Scheduling Problem (RS-SSP) for optimising the effectiveness of the capacity usage at service locations. Experimental testing of the RS-SSP model on real-life instances of the Dutch railways showing an increase in servicing capacity.